CRIMINAL LAW ASPECTS OF THE COUNCIL OF EUROPE CONVENTION ON PREVENTING AND COMBATING VIOLENCE AGAINST WOMEN AND DOMESTIC VIOLENCE - Samardžić, Stefan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
The Istanbul Convention is a part of domestic legislation of the Republic of Serbia. The Constitution provides for direct application of the Convention, provided that it is in compliance with the provisions of the highest law of Serbia. Apart from the focal point relating to the question of compliance of or the need to comply the national criminal legislation with the Convention, the aim of the article is to analyze the quality of the relevant provisions of the Convention from the criminal law point of view and with particular reference to the quality of the translation of the Convention into the Serbian language. In order to define obligations of the Republic of Serbia that have arisen after the ratification of the Istanbul Convention we dealt, to a certain degree, with the problem of direct application of the international law to the national criminal law system, along with providing a detailed analysis of this international treaty.